The external dimension of EU justice and home affairs: Tools, processes, outcomes - Thierry Balzacq (Center for Social and Economic Research (CASE), 2008)
This working document offers a conceptual framework for understanding the processes underpinning the external dimension of EU Justice and Home Affairs (ED-JHA). Practically, it defines how the export of JHA principles and norms inform the geopolitical ambitions of the EU, i.e. the use of space for political purposes, or the control and management of people, objects and movement. The author begins by investigating how the ENP reconfigures the ED-JHA, and then goes on to discuss various conceptual stances on governance, specifically institutionalism, constructivism, and policy instruments. To conclude he traces the evolution of this external dimension, emphasising, whenever possible, its continuities and bifurcations. Overall, the aim is to ascertain the extent to which conceptual designs clarify or advance our knowledge of the contents and rationales of the ED-JHA.
Keywords: 330; neighbourhood policy; international politics; geopolitics; migration; immigration; European security; policy instruments; governance; Security and Justice; Justice and Home Affairs; EU-Politik; EU-Nachbarstaaten; Öffentliche Sicherheit; EU-Staaten